The oversight of fire prevention in an enterprise - Marian Kopczewski; Marek Tobolski (Foundations of Management, 2013)
An efficiently working fire protection system in an enterprise, a work place or an institution guarantees the proper execution of fire protection duties. Its proper organisation is of key importance. The conditions of the proper organisation of the fire protection system in a given organisational unit are above all the universality in the scope of using applicable provisions, knowledge of applicable provisions, appropriately exercised supervision of usage of applicable provisions, orders and established rules of conduct. The aim of this paper is to specify the most important duties of owners, users or managers in providing protection against fire or other local risks. This results from the fact that given the variety of operating enterprises, the character of their activity, kind of production and used technology, size, fire risk, etc. it is not possible to determine a standard model of a fire protection system for a particular work place.
Keywords: 650; fire protection; fire safety; preventive measures; fire